On Lagrange Multiplier Rules for Set-Valued Optimization Problems in the Sense of Set Criterion. (25th April 2020) - Amahroq, Tijani; Oussarhan, Abdessamad; Syam, Aicha
Abstract: In this paper, we obtain a new scalar representation of set-valued optimization problems by using a criterion of solution introduced by Kuroiwa, this criterion is a weaker version of Pareto efficient solution. Following this scalarization, we establish necessary optimality conditions in terms of Fritz John multipliers as well as Karush-Kuhn-Tucker multipliers. Moreover, we give sufficient optimality conditions.